Awareness and the Perceived Socio-economic Outcomes of ’Eco-tourism’: a Study in the Corbett Area - Vigneshwarie, R.; Singh, B. B. (Indian Forester, 2011)
There was a wide variability in the levels of awareness about eco-tourism among the tourists, the local villagers and the forest officials. Of the two components, viz. environmental and social welfare, the latter was not understood by many. While nature, wildlife and its products were the aesthetic needs of the tourists, the indigenous values formed a part of their recreation, physical and mental relaxation. Locally available services like guidance, hospitality, asset maintenance, product sales, etc. helped in meeting these needs. This resulted in overall improvement in the quality of life. Better promotion and training strategies with adequate planning and ensured local cooperation were the prerequisites to bring the dual effects on forest conservation and community development.